SPECTRUM OF XY DISORDERS OF SEX DEVELOPMENT IN PAKISTAN: XY Disorders of Sex Development - Haroon, Dr Zujaja Hina; Ijaz, Aamir; Haroon, Muhammad Asad; Asif, Naveed; Malik, Qudrat Ullah; Ayyub, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the clinico-endocrinal spectrum of XY Disorders of Sex Development (DSD) according to the new classification in our population. Study Design: Cross sectional study. Place and Duration of Study: Department of Chemical Pathology and Endocrinology Armed Forces Institute of Pathology Rawalpindi, from Jan 2012 to Aug 2015. Material and Methods: A total of 151 patients who reported for work-up of DSD during 2012-2015 and labeled XY on karyotyping were included in the study. Patients without karyotyping results, mixed sex chromosome or XX karyotypes were excluded from the study. Patient’s clinical features and results of serum hormones i.e. LH, FSH, Testosterone, 17 hydroxy progesterone, DHEAS and hCG stimulation test were analyzed. Results: Out of 151 patients of XY DSD, 68 (45%) patients were diagnosed as partial androgen insensitivity syndrome (PIAS), 18 (12%) as isolated micropenis, 25 (16.6%) as partial gonadal dysgenesis, 12 (7.9%) as hypogonadotropic hypogonadism, 11 (7.2%) as primary hypogonadism, 13 (8.6%) as complete androgen insensitivity syndrome (CAIS) and 4 (2.6%) as 5α reductase deficiency. There was a wide variation in age of presentation ranging from three months to twenty five years with the median age of 9.5 years. Nineteen (12.6%) were raised as female and 132 (87.4%) were raised as male. The main complaints at presentation were ambiguous genitalia (30.5%), undescended testes (21.2%), delayed puberty (19.2%), micropenis (16.6%), inguinal hernia (8.6%), and primary amenorrhea (3.9%). Conclusion: Androgen insensitivity syndrome (AIS) in its various forms is the commonest of all XY DSD. All DSD including AIS require complete investigations in a tertiary care setup.